2019
DOI: 10.21079/11681/31449
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of insulated pavements to prevent frost damage

Abstract: Frost heaving is a constant burden on any facility in cold regions, causing accelerated deterioration of roadways and annual maintenance, leading to costly repairs. Insulated pavements have been demonstrated as cost effective in several civilian locations, and have shown exceptional resistance to compression and water absorption. The objective of this study was to evaluate the effectiveness of insulated pavement in eliminating the impact of frost action on roadways for the purpose of reducing annual roadway ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
0
0
Order By: Relevance
“…More specifically, Hasanuzzaman et al (2023) demonstrated that A. nodosum extracts increased the Cd toxicity tolerance of plants, inducing an increase in plant biomass. BG treatment can also lead to improve growth, stress tolerance, yield, and nutrient uptake (Mondragón‐Valero et al, 2019; Pascoalino et al, 2021; Saa et al, 2015; Torres et al, 2015). In an experiment with regular applications (three times a month) of a boron‐based fertilizer such as the BG treatment, Esteves et al (2022) revealed a decrease of oxidative damage to the DNA due to abiotic stresses, which increased photosynthetic area and, consequently, yield.…”
Section: Discussionmentioning
confidence: 99%
“…More specifically, Hasanuzzaman et al (2023) demonstrated that A. nodosum extracts increased the Cd toxicity tolerance of plants, inducing an increase in plant biomass. BG treatment can also lead to improve growth, stress tolerance, yield, and nutrient uptake (Mondragón‐Valero et al, 2019; Pascoalino et al, 2021; Saa et al, 2015; Torres et al, 2015). In an experiment with regular applications (three times a month) of a boron‐based fertilizer such as the BG treatment, Esteves et al (2022) revealed a decrease of oxidative damage to the DNA due to abiotic stresses, which increased photosynthetic area and, consequently, yield.…”
Section: Discussionmentioning
confidence: 99%